2 Effects of sorafenib treatment on HNSCC cells in combination with cisplatin based-chemoradiation. Issue 5 (May 2015) - Möckelmann, N.; Kriegs, M.; Dikomey, E.; Knecht, R.
<x xml:space="preserve">Abstract</x> Background To improve the outcome of patients with squamous cell carcinoma of the head and neck (HNSCC) and reduce the side effects of radiochemotherapy, the combination of target therapeutics with established chemoradiation protocols is under investigation. Sorafenib, a multikinase inhibitor, has a cytotoxic and antiproliferative effect as a monotherapy and acts as a radiosensitizer of HNSCC cell lines. As cisplatinbased chemoradiation is the standard treatment for locally advanced HNSCC, the aim of this study was to identify the influence of sorafenib on cisplatin + radiation treatment in HNSCC cell lines and to determine the effects on normal cells, to assess potential dose limiting toxicities. Material and methods Two different HNSCC cell lines (UT-SCC42A and UT-SCC42B) were treated by combination of Sorafenib (10 <alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwrc1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>M; Nexavar®, Bayer) and Cisplatin (1–10<alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwqkn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>M) with/without irradiation (2–6 Gy). Cell number was assessed to determine the proliferation rate and colony formation assay was performed for estimation of cell survival. Fibroblasts (F180) were treated similarly to evaluate the cytotoxicity in non-tumor cells. Results Cisplatin has a dose-dependent antiproliferative effect in both cell lines. The growth inhibitory effect is clearly increased by addition of Sorafenib in a dose of 5 <alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwkr9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>mol/l, according to a synergistic effect to cisplatin. In colony formation assay Cisplatin and Sorafenib have a dose-dependent cytotoxic effect in both cell lines. The combined treatment shows a sensitization of UT-SCC42A & 42B cells by Sorafenib against Cisplatin treatment, according to a chemosensitization. In both tested cell lines we observe a radiosensitization by sorafenib (10 <alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwsp5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>mol/l) in presence of cisplatin (all tested doses), in contrast to only a minor radiosensitizing effect on HNSCC cells by Cisplatin alone. Fibroblasts (F180) were not affected by Sorafenib in terms of cell inactivation investigated in the colony formation assay. Conclusion Sorafenib acts as a radio- and chemosensitizer in two tested cell HNSCC cell lines and has no cytotoxic effect on normal fibroblasts. Therefore the combination of sorafenib with cisplatin-based chemoradiation may improve the efficacy of HNSCC treatment in terms of survival outcome and side effects.